The interplay of eco-labels and price cues: Empirical evidence from a large-scale field experiment in an online fashion store. (1st November 2022) - Feuß, Sebastian; Fischer-Kreer, Denise; Majer, Johann; Kemper, Jan; Brettel, Malte
Abstract: Even though eco-labels are a promising means to support consumers in making sustainable choices, insights into the effectiveness of eco-labels in combination with conventional marketing tools are scarce. This field study (a) investigates the effect of eco-labels on consumers' actual purchase behavior in an online fashion store, (b) examines the moderating role of price premiums, and (c) reveals a three-way interaction between eco-labels, price premiums, and discounts. Based on 58, 000 actual purchase decisions from a large-scale field experiment, the results indicate a beneficial effect of eco-labels on consumer purchases and that higher price premiums can even reinforce the positive effect of eco-labels. The empirical findings also suggest that discounts only increase purchases for eco-labeled products in combination with high price premiums, but not with low price premiums. The present study has important implications for research on eco-labels and their interplay with other marketing cues and provides valuable guidance to marketers and policymakers on how to price eco-labeled products. Highlights: - This study examines the interactive effects of eco-labels and prices on purchases - Actual consumer behavior was observed in a controlled large-scale field experiment - The findings show that eco-labels increase purchase probability - High price premiums strengthen this eco-label effect - The results also suggest a three-way interaction of eco-labels, price premiums, and discounts